Vertical Stratification of Chiropterans in Dakama Forest and an Examination of Edge–Interior Habitats in Guyana - Ramlochan, Anita; Ansari, Abdullah Adil (Proceedings of the Zoological Society, 2024)
An investigation of bat species assemblage with regards to vertical stratification; trophic guild composition; and edge effect, was conducted in a forest fragment at Bamia, Guyana. Bats were sampled using mist-nets placed at two heights (canopy and understory) and two habitats (interior and edge) along a 1.214 km stretch at 200 m intervals. A survey effort of 40,694.4 m 2 h yielded 312 captures representing 23 species from three families. The canopy recorded a total of 77 individuals representing 14 species with 3 exclusives, while the understory recorded 235 individuals representing 20 species with 9 exclusives. The Bray–Curtis non-metric multidimensional scaling (Stress 0.104, r 2 = 0.989) indicated a well-marked separation in bat assemblages in the understory and canopy strata, and perMANOVA analysis indicated a significant difference in species composition in the understory and canopy strata (pseudo F = 9.896, p value 0.028). Seven trophic guilds were documented with frugivores (47.8% captures; 11 species) being the most abundant and speciose guild followed by the aerial insectivores and gleaning insectivores respectively. Edge habitats recorded 165 individuals with 9 exclusives, while 70 individuals with no exclusives were noted in the interior regions. Although, no graphically visible separation was seen among some edge and interior plots using the NMDS, some degree of dissimilarity was noted for the other sites. Analysis using the perMANOVA indicated a significant difference in species composition in the edge and interior habitats (pseudo F = 4.795, p value 0.024). This study further emphasizes the importance of surveying the vertical and horizontal space of the forest in an effort to detect and quantify all species present in the area.